Problems and Prospects of Innovative and Investment Development of Modern Russia - Izmailova, Marina Alekseevna; Reshetova, Tatiana Yakovlevna; Rukina, Irina Mihailovna; Seifullaeva, Maissa Emirovna; Yunusov, Ildar Albertovich (International Journal of Economics and Financial Issues, 2016)
The necessity for the modernization of the Russian economy based on its transition to the innovative development model is actualized in this article. The urgency of measures on the amendment of the economic policy in related areas of innovation and investment activity, as well as the measures on establishment of the conditions required for the settlement of the innovation and reproduction problems of modernization of the national economy is substantiated. The scientific analysis of the economic foundations of the model of innovative development of Russia is performed. The results of the comparative analysis of possible scenarios for innovation and investment development of the national economy and their forecast results are interpreted based on the identification of the major trends in the economic development in the national and global markets. The main problems, trends and conditions to increase the investment activity in order to achieve the sustainable development of the Russian economy on an innovative basis are described. The description of the instruments of state support of the innovation and investment activity is provided. The prospects of public-private partnership in the implementation of the priority programs of innovative development and important infrastructure projects are described. The conclusion of the inevitability of Russia's transition to a new technological system, requiring the formation of new scientific and industrial policies focused on innovation and technological upgrading of the entire economic landscape, imparting the actually innovative nature to the economy is made. Keywords: innovation, investment activity, development scenarios, innovation policy, technological way. JEL Classifications: Q00, F63, E60, H54.